1997
DOI: 10.1002/jor.1100150512
|View full text |Cite
|
Sign up to set email alerts
|

Laxity and flexibility of the ankle following reconstruction with the Chrisman‐Snook procedure

Abstract: The effect of reconstruction of the anterior talofibular ligament with the Chrisman-Snook procedure on neutral zone laxity (anterior-posterior displacement at low loads) and flexibility (a measure of the nonlinear load-displacement response) of the ankle was investigated in vitro during the anterior drawer test. Neutral zone laxity was defined as the magnitude of anterior-posterior displacement of the ankle joint at +/- 2.5 N of applied load. The flexibility parameter was defined as the slope of a line between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Most of these studies report that a tendon transfer procedure limits the range of ankle motion and prevents neither anterior talar translation nor talar tilt [3,23,30,33,44]. Most of these studies report that a tendon transfer procedure limits the range of ankle motion and prevents neither anterior talar translation nor talar tilt [3,23,30,33,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies report that a tendon transfer procedure limits the range of ankle motion and prevents neither anterior talar translation nor talar tilt [3,23,30,33,44]. Most of these studies report that a tendon transfer procedure limits the range of ankle motion and prevents neither anterior talar translation nor talar tilt [3,23,30,33,44].…”
Section: Discussionmentioning
confidence: 99%
“…This impaction force explains the cartilage damage which can subsequently lead to degenerative changes[3,12,23, 30,33,39,44, 46]. It has been demonstrated that in supination trauma cartilage damage occurs in 65% at the medial talar facet and tip of the medial malleolus[46].…”
mentioning
confidence: 99%
“…1,[18][19][20][21][48][49][50][51][52][53][54] Use of an anatomic reconstruction has replaced the historical tenodesis procedures such as the Evans, Watson-Jones, Chrisman-Snook, and others that have been shown anatomically and in long-term clinical studies to limit subtalar motion. 8,16,17,22,[55][56][57][58][59][60][61][62][63] In the authors' experience, mistakes in harvesting involve difficulty in isolating the tendon (approach) and amputating the tendon short. The type of anesthetic used in conjunction with this procedure is important.…”
Section: Surgical Technique Brostrom Proceduresmentioning
confidence: 99%
“…1 These patients frequently require surgical intervention, most commonly in the form of a Brostrom-Gould lateral ankle ligament reconstruction. [12][13][14][15] They are primarily reserved for patients with generalized ligamentous laxity, heavy patients, or for revision cases. [8][9][10][11] These techniques tend to produce stiffness, scarring, can result in nerve injury, and can eventually lead to degenerative changes of the ankle and subtalar joints.…”
Section: Historical Perspectivementioning
confidence: 99%